The production of formaldehyde and hydroxyacetone in methacrolein photooxidation: New insights into mechanism and effects of water vapor - Y.N. Xing; H. Li; L.B. Huang; H.H. Wu; H.Q. Shen; Chen, Z. M. (Journal of Environmental Sciences, 2018)
Methacrolein (MACR) is an abundant multifunctional carbonyl compound with high reactivity in the atmosphere. In this study, we investigated the hydroxyl radical initiated oxidation of MACR at various NO/MACR ratios (0 to 4.04) and relative humidities (< 3% to 80%) using a flow tube. Meanwhile, a box model based on the Master Chemical Mechanism was performed to test our current understanding of the mechanism. In contrast to the reasonable predictions for hydroxyacetone production, the modeled yields of formaldehyde (HCHO) were twice higher than the experimental results. The discrepancy was ascribed to the existence of unconsidered non-HCHO forming channels in the chemistry of CH3C(=CH2)OO., which account for approx. 50%. In addition, the production of hydroxyacetone and HCHO were affected by water vapor as well as the initial NO/MACR ratio. The yields of HCHO were higher under humid conditions than that under dry condition. The yields of hydroxyacetone were higher under humid conditions at low-NOx level, while lower at high-NOx level. The reasonable explanation for the lower hydroxyacetone yield under humid conditions at high-NOx level is that water vapor promotes the production of methacrolein nitrate in the reaction of HOCH2C(CH3)(OO.)CHO with NO due to the peroxy radical-water complex formation, which was evidenced by calculational results. And the minimum equilibrium constant of this water complex formation was estimated to be 1.89 × 10−18 cm3/molecule. These results provide new insights into the MACR oxidation mechanismand the effects of water vapor.